Pemberian Ganti Rugi Terhadap Pembebasan Lahan Bendungan Manikin di Desa Baumata Timur Kecamatan Taebenu Kabupaten Kupang - Yosaphat Patrick Delano Fernandez; Novita Scolastika Totnay; Benediktus Petter Lay (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The land that has been needed for the life of the Indonesian people is getting less and less, plus the population density of the Indonesian people is increasing, this makes land very important. Along with the increasing importance of land for the life of the Indonesian people, then in Article 33 paragraph (3) of the 1945 Constitution, it reads that: Earth and water and the natural resources contained therein are controlled by the State and used for the greatest prosperity of the people. Problems relating to land, especially in Indonesia, are very, very complex, because what we all know is that land is the main resource and factor of production for life at large, so it cannot be separated from various aspects of human life. The development of the current development is very rapid, especially the construction of dams to support the smooth running of existing needs in accordance with the function of the dam. In land acquisition carried out by the committee that has been formed, it is hoped that it can work with humane approaches. In forming the committee for land acquisition to be acquired, it is necessary to involve one of the influential community leaders, this is to facilitate the smooth running of the land acquisition process. In land acquisition involving community leaders is something that really needs to be done because those who know the character and nature of the community are the community itself, which was started by influential figures.